Três ensaios sobre a agroindústria canavieira no Brasil pós-desregulamentação - Rissardi Júnior, Darcy Jacob (2015)
The period of post-deregulation of the sugarcane agroindustry in Brazil makes clear the technological paradigm advancement, in which the improvement of technological development of productive sites becomes urgent in a more competitive market, substantiating leadership and contributing for a new dynamic in the sector. Considering it, this thesis proposes a new formatting (in PGDRA ) to analyze some aspects of sugarcane agroindustry in this period, based on three papers concatenated that look into, in a general context, deepen the knowledge about the dynamic of this important sector facing, mainly, a new organization that changed the market conditions. The first paper looks for analyzing concisely and historically the evolution of sugarcane agroindustry post-deregulation (1990 2014). The second paper tries to estimate and analyze the modernization and specialization process experienced by sugarcane agroindustry from the 1990 s, using the factor analyzes procedure by means of the principal components method. With an overview from Brazil with historical perspective and from the measuring of its modernization and specialization process, the third paper makes empirical analyzes from a case study, looking into new ways of organizing according to new institutionalism and new corporatism. The results of the first paper show three distinct phases. In the first phase, 1986/1987 to 1995/1996, there was the slowdown and crisis of Proalcool Program and break down of subsidizing paradigm. The second phase, 1996/1997 to 2002/2003, there was an increasing of deregulation, showing the structural weakness and the emerging of a variety of interests. Finally, the third phase, 2003/2004 to 2013/2014, there was the resumption of ethanol with flex-fuel market, loads of Foreign Direct Investments (FDI) and lack of planning from the Federal government in the market of gasoline price, that discourage the ethanol use. In the second paper, the results show that it wasn t without intention that many plants and distilleries close down in Brazil, because many results from factors F1 (modernization and specialization process from sugarcane industry) and F2 (agricultural and industrial index) were negatives. In the general context of this multivariate analyze, São Paulo remained as the state with supreme position in sugarcane production. In the third paper the results testify, under the New Institutional Economics view, the importance of formal contracts and contractual governance structures in the full scope of this sector in the state of Paraná. It is proved, under the new corporatism view, the strategic role of business organizations about the attainment of public policies of sectional interests and the importance of Brazilian Chamber of the Productive Chain of Sugar and Alcohol, under the jurisdiction of the Ministry of Agriculture, Livestock and Food Supply ( MAPA ), defending private interests from private agents.